Mr. Paradis - Leonard, Elmore (New York : Morrow, 2004)
Mr. Paradise follows a smart Victoria$1 (Bs Secret model$1 (Bs attempt to score big after surviving a double murder in a millionaire$1 (Bs mansion$1! =(Bwith a lonely cop acting as spoiler.s
83374
Keywords: Police -- Michigan -- Detroit -- Fiction; Aged men -- Crimes against -- Fiction; Young women -- Fiction; Witnesses -- Fiction; Detroit (Mich.) -- Fiction; Mystery fiction